Heywood Broun, Benjamin Stolberg, and the politics of American labor journalism in the 1920s and 1930s - Phelps, Christopher (Duke University Press, 2017)
Between the First and Second World Wars, Heywood Broun (1888-1939) and Benjamin Stolberg (1891-1951) were labor journalists when the newspaper industry was consolidating into chains and industrial unionism was gaining in American society. A comparison of their lives and writings in the 1920s and 1930s illuminates the politics behind news coverage of labor. Suspicious of the Communist Party, Stolberg ultimately clashed with Broun, the quintessential Popular Front left-liberal, over the Congress of Industrial Organizations (CIO). The two were similar, however, in framing labor positively, unlike much of the rest of the press, while eschewing any journalistic ethos of “impartiality.”